2013
DOI: 10.2522/ptj.20120127
|View full text |Cite
|
Sign up to set email alerts
|

Evaluative Frailty Index for Physical Activity (EFIP): A Reliable and Valid Instrument to Measure Changes in Level of Frailty

Abstract: The EFIP is a reliable and valid instrument to evaluate the effect of physical activity on frailty in research and in clinical practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
49
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(50 citation statements)
references
References 39 publications
1
49
0
Order By: Relevance
“…More recently, de Vries et al [76] have created a frailty index based on the deficit which was found to significantly correlate with measures of strength and mobility including the TimedUp and Go test (r=0.61, p=0.00), Performance Orientated Mobility Assessment (r=-0.70 p=0.00) and the Cumulative Illness Rating Scale for Geriatrics (r=0.66 p=0.00), however the study was small in size (n=24) and further information on how the instrument performs over time and in evaluating outcomes from interventions is required.…”
Section: How Is Frailty Identified or Diagnosed?mentioning
confidence: 99%
“…More recently, de Vries et al [76] have created a frailty index based on the deficit which was found to significantly correlate with measures of strength and mobility including the TimedUp and Go test (r=0.61, p=0.00), Performance Orientated Mobility Assessment (r=-0.70 p=0.00) and the Cumulative Illness Rating Scale for Geriatrics (r=0.66 p=0.00), however the study was small in size (n=24) and further information on how the instrument performs over time and in evaluating outcomes from interventions is required.…”
Section: How Is Frailty Identified or Diagnosed?mentioning
confidence: 99%
“…Psychological functioning was assessed with the Hospital Anxiety and Depression Scale (HADS) (42). The Evaluative Frailty Index for Physical activity was used to measure the level of frailty (43).…”
mentioning
confidence: 99%
“…The Older Persons and Informal Caregivers Survey Minimum DataSet (TOPICS-MDS) [65] is administered to assess activities of daily living and mood. Quality of life is measured with the Dementia Quality of Life Instrument [66] and frailty by using the Evaluative Frailty Index for Physical Activity [67]. These outcome measures are assessed at pre-test (T0) and post-test (T2).…”
Section: Methodsmentioning
confidence: 99%